Effectiveness of Regulation of The Minister of Trade Number 40 Of 2022 Concerning Goods Prohibited from Export and Goods Prohibited from Import in The Tabanan Frog Market - Ni Made Ayu Dwi Ardani; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Warmadewa Press, 2024)
This research examines the factors contributing to the ongoing trade of imported used clothing at Tabanan Regency’s Frog Market and evaluates the enforcement of Minister of Trade Regulation Number 40 of 2022, which prohibits the import and sale of such items. Imported used clothing poses a threat to local MSMEs and is flagged as a potential health risk due to its contact with human skin. However, the Frog Market, established in the early 2000s, remains a bustling hub for secondhand clothing, fueled by consumer demand for affordable, quality apparel. The study employs an empirical legal research method, incorporating socio-legal and legislative approaches through field observations and interviews. Findings reveal that economic necessity, unique fashion appeal, and environmental considerations drive consumers to purchase used clothing. Additionally, sellers leverage flexible, informal sales channels, including online groups, to sustain their businesses. Despite awareness of the legal restrictions, the economic reliance on thrifting poses challenges for regulation enforcement. The study concludes that for regulatory effectiveness, enhanced public awareness, law enforcement engagement, and consideration of local socio-economic realities are essential. These findings provide insights for policymakers aiming to balance legal mandates with the socio-economic impact on communities reliant on this trade.